Hubungan Antara Pola Makan Dengan Kejadian Gastritis Pada Remaja - Tati Karyawati; Slamet Wijaya Biantoro (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Teenagers are often trapped in unhealthy and irregular eating patterns, even to the point of experiencing eating disorders. Eating disorders due to being busy with school assignments and other life burdens, make them tend to experience stomach problems, namely ulcers or gastritis. The aim of this research is to determine the relationship between eating patterns and the incidence of gastritis in adolescents at SMA Al Hikmah 2 Brebes. This research is a quantitative research with a descriptive correlation design using a cross sectional approach. The sampling technique in this research is Simple Random Sampling. The number of samples in this research was 71 respondents using the Slovin formula, the measuring tool used in this research was a questionnaire. The research results showed that 45 respondents (63.4%) had good eating patterns and 26 respondents (36.6%) had poor eating patterns. From the results of statistical testing using the chi Square statistical test, the p-value = 0.000 (p<0.005) was obtained, so there is a relationship between diet and the incidence of gastritis in teenagers at SMA Al Hikmah 2 Brebes. Suggestions from research are that teenagers can pay attention to their diet to prevent gastritis.